2016
DOI: 10.1249/jes.0000000000000074
|View full text |Cite
|
Sign up to set email alerts
|

Fiber Type-Specific Effects of Dietary Nitrate

Abstract: Dietary nitrate supplementation increases circulating nitrite concentration, and the subsequent reduction of nitrite to nitric oxide is promoted in hypoxic environments. Given that PO2 is lower in Type II compared with Type I muscle, this article examines the hypothesis that the ergogenicity of nitrate supplementation is linked to specific effects on vascular, metabolic, and contractile function in Type II muscle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
110
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(131 citation statements)
references
References 41 publications
11
110
1
2
Order By: Relevance
“…Instead, the ergogenic effect of BRJ may be better explained by other physiological changes. Interestingly, recent murine model studies have identified effects of NO 3 − which appear to be selective to type II muscle (for review, see Jones et al 2016), and may be of mechanistic relevance in the present study given the likely high recruitment of type II fibers during the 1500 m TT (Essén 1978;Sale 1987). NO 3 − supplementation was reported to augment blood flow and thus O 2 delivery to type II muscle in exercising rats (Ferguson et al 2013(Ferguson et al , 2015.…”
Section: Effects Of Brj On 1500 M Tt Performancementioning
confidence: 51%
See 1 more Smart Citation
“…Instead, the ergogenic effect of BRJ may be better explained by other physiological changes. Interestingly, recent murine model studies have identified effects of NO 3 − which appear to be selective to type II muscle (for review, see Jones et al 2016), and may be of mechanistic relevance in the present study given the likely high recruitment of type II fibers during the 1500 m TT (Essén 1978;Sale 1987). NO 3 − supplementation was reported to augment blood flow and thus O 2 delivery to type II muscle in exercising rats (Ferguson et al 2013(Ferguson et al , 2015.…”
Section: Effects Of Brj On 1500 M Tt Performancementioning
confidence: 51%
“…Recent data from murine models suggest that NO 3 − supplementation elevates blood flow and oxygenation (Ferguson et al 2013(Ferguson et al , 2015, and increases calcium (Ca 2+ ) handling protein expression and force production (Hernandez et al 2012) in type II muscle only (for review, see Jones et al 2016). Therefore, the beneficial effects of NO 3 − supplementation might be restricted to, or most pronounced during, exercise where type II fibers are predominantly recruited (Breese et al 2013;Bailey et al 2015;Coggan et al 2015), such as during short duration exercise where a higher relative work rate can be adopted (Essén 1978;Sale 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Further, there is evidence from murine model investigations that nitrate supplementation may enhance tissue blood flow [41,42] and muscle contractile function [9] preferentially in type II muscle fibres. It is therefore possible that nitrate supplementation is more effective during shorter more high-intensity exercise, during which these muscle fibres are more heavily recruited [9,[43][44][45]64], or else in individuals with greater distribution of type II muscle fibres [43]. The time-trial duration employed in this study (< 6 minutes) was considerably less than other investigations (~ 17 -48 minutes) which have not observed an ergogenic effect of nitrate supplementation in hypoxia [38][39][40], and may be important.…”
Section: Effect Of Nitrate Supplementation On Running Performance In mentioning
confidence: 75%
“…Evidence from murine models suggests that the effects of dietary nitrate supplementation may be fibre type specific, increasing muscle perfusion and oxygenation [41,42], and enhancing calcium handling and force production [9] in type II muscle fibres only, as may be recruited during high-intensity exercise (for review, see Jones et al [43]). Moreover, nitrate supplementation has been demonstrated to elicit beneficial effects when the contribution of type II muscle towards force generation is high, including at fast but not slow muscle contraction frequencies [44], and during the transition from moderate to severe but not unloaded to moderate intensity exercise [45].…”
Section: Introductionmentioning
confidence: 99%
“…This may be a consequence of the higher baseline pool of NO metabolites already present in this cohort (Vassalle et al, 2003), the elevated activity and presence of the NOS enzymes (McConell et al, 2007), or greater proportion of type I muscle fibres, which are believed to be less receptive to the effects of nitrate supplementation (Ferguson et al, 2013;Hernandez et al, 2012;Jones et al, 2016). …”
Section: Discussionmentioning
confidence: 99%